2013
DOI: 10.3390/rs5073516
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture & Snow Properties Determination with GNSS in Alpine Environments: Challenges, Status, and Perspectives

Abstract: Moisture content in the soil and snow in the alpine environment is an important factor, not only for environmentally oriented research, but also for decision making in agriculture and hazard management. Current observation techniques quantifying soil moisture or characterizing a snow pack often require dedicated instrumentation that measures either at point scale or at very large (satellite pixel) scale. Given the heterogeneity of both snow cover and soil moisture in alpine terrain, observations of the spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…Gutmann et al (2012) evaluated this technique successfully for an entire winter season. Boniface et al (2015) and Larson (2016) used networks of geodetic stations to derive HS around the stations at numerous locations in the western U.S. Botteron et al (2013); Cardellach et al (2011) andJin et al (2014) give an overview on several GNSS reflectometry approaches. Even though obstacles might influence the measurements, Vey et al (2016) reported that this technique might also be applicable for urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Gutmann et al (2012) evaluated this technique successfully for an entire winter season. Boniface et al (2015) and Larson (2016) used networks of geodetic stations to derive HS around the stations at numerous locations in the western U.S. Botteron et al (2013); Cardellach et al (2011) andJin et al (2014) give an overview on several GNSS reflectometry approaches. Even though obstacles might influence the measurements, Vey et al (2016) reported that this technique might also be applicable for urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Even specific GNSS-R space-based missions have been planned by different space agencies [3,16,17]. Furthermore, more remote sensing applications have been also proposed and validated through experimental campaigns, such as: soil moisture monitoring [7,18,19,20,21,22,23,24,25], snow monitoring [26,27,28,29,30,31,32], sea-ice monitoring [33,34], ground and calm water altimetry [35,36,37,38,39,40,41,42,43] and biomass estimation [44,45]. …”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the antenna position is known, we can compute the position of the surface of reflection. This approach provides precise localization and dating of the measures that allows for spatio-temporal comparison of water levels and snow cover, respectively [58]. These parameters are very important for flood monitoring and avalanche prevention, as well as for hydroelectric companies.…”
Section: Introductionmentioning
confidence: 99%